Terapi Senam Terhadap Penurunan Nyeri Osteoartritis Pada Lansia di Panti Jompo Wreda Dharma Kasih - Gulo, Sinansari; Sukmaningtyas, Wilis; Firdaus, Eza Kemal (Yayasan Daarul Huda Kruengmane, 2024)
Background. Elderly is someone who reaches the age of 60 years and above. The elderly will also experience health problems caused by aging, usually affecting the joints, namely osteoarthritis. Osteoarthritis is chronic inflammation in the joints that causes tissue damage to the cartilage. There are several factors that cause osteoarthritis, namely age and gender, obesity, genetics, joints, muscle strength, and knee alignment. Osteoarthritis in the elderly can be reduced or treated with exercise therapy. Based on a pre-survey at the Budi Dharma Kasih Nursing Home, it was found that more than half of the elderly experienced osteoarthritis pain due to a lack of understanding in reducing this pain. Objective. This community service (PkM) activity aims to implement exercise for the elderly. Method : This PkM method is carried out by providing Ostearthritis material, then exercise therapy, followed by a discussion containing a question and answer session regarding the material presented, as well as an evaluation using pre and post questionnaires after exercise therapy. Results. The results obtained after carrying out exercise therapy activities for the elderly were an increase in pain with the moderate pain group before implementation amounting to (0.0%) after implementation increasing by (55.6%), the severe pain group before implementation amounting to (100.0%) after implementation it decreased by (44.4%). Outer. There are three expected outcomes from this PkM activity, namely, 1. The elderly can apply exercise therapy 2. Videos containing exercises, 3. Publication of community service articles.